Mapping ecosystem service and biodiversity changes over 70 years in a rural English county. Issue 4 (12th June 2013) - Jiang, Mingkai; Bullock, James M.; Hooftman, Danny A. P.
Summary: Biodiversity and ecosystem services continue to be compromised by land‐use change, which is often focussed on enhancing agricultural production. Assessment of losses would be aided by analyses of temporal changes in the extent and spatial pattern of services and biodiversity. To date, no studies have mapped long‐term changes in ecosystem services using historical maps. We mapped changes between the 1930s – before the considerable intensification of land use in the UK starting in the 1940s – and 2000 in climate change amelioration services (carbon storage), provisioning services (agriculture and forestry) and plant species richness (biodiversity) for Dorset, a rural English county. We combined land‐use maps (1‐ha resolution) with multiple proxies of service delivery for the 10 different Broad Habitats in the region. Biodiversity was mapped using plant survey data from the two time periods. We used bootstrapping to include uncertainty due to the different proxies and Gini coefficients to quantify statistical changes in spatial pattern. Overall, we found significant increases in agricultural provisioning and large losses in biodiversity over the period, which reflect widespread conversion and intensification of land use. We found no change in Dorset's carbon store, because carbon lost through land‐use intensification was balanced by increases in woodland over the 20th century. The carbon storage and the delivery of provisioning services both became more unequally distributed, indicating a change from relatively homogeneous delivery of services to concentration into hotspots. The maps from the year 2000 showed spatial dissociation of hotspots for carbon, provisioning and biodiversity, which suggests that, compared to the 1930s, modern, intensive land use creates conflicts in delivery of multiple services and biodiversity. Synthesis and applications . Detailed maps of historical changes in location‐specific service delivery and biodiversity provide valuable information for land‐use planning, highlight trade‐offs and help to identify drivers. Furthermore, historical maps provide an important baseline to indicate the suitability and potential success of suggested actions, such as habitat restoration, and their relevance to traditional land use. Various frameworks could be informed by our approach, including the ecosystem service aims of the EU biodiversity strategy and the newly created UK Nature Improvement Areas. Abstract : Detailed maps of historical changes in location‐specific service delivery and biodiversity provide valuable information for land‐use planning, highlight trade‐offs and help to identify drivers. Furthermore, historical maps provide an important baseline to indicate the suitability and potential success of suggested actions, such as habitat restoration, and their relevance to traditional land use. Various frameworks could be informed by our approach, including the ecosystem service aims of the EU biodiversity strategy and the newly created UK Nature Improvement Areas.